Implicit and Explicit Attention to Pictures and Words: An fMRI-Study of Concurrent Emotional Stimulus Processing - Flaisch, Tobias; Imhof, Martin; Schmälzle, Ralf; Wentz, Klaus-Ulrich; Ibach, Bernd; Schupp, Harald T. (Frontiers in Psychology, 2015)
The present study utilized functional magnetic resonance imaging (fMRI) to examine the neural processing of concurrently presented emotional stimuli under varying explicit and implicit attention demands. Specifically, in separate trials, participants indicated the category of either pictures or words. The words were placed over the center of the pictures and the picture-word compound-stimuli were presented for 1500 ms in a rapid event-related design. The results reveal pronounced main effects of task and emotion: the picture categorization task prompted strong activations in visual, parietal, temporal, frontal, and subcortical regions; the word categorization task evoked increased activation only in left extrastriate cortex. Furthermore, beyond replicating key findings regarding emotional picture and word processing, the results point to a dissociation of semantic-affective and sensory-perceptual processes for words: while emotional words engaged semantic-affective networks of the left hemisphere regardless of task, the increased activity in left extrastriate cortex associated with explicitly attending to words was diminished when the word was overlaid over an erotic image. Finally, we observed a significant interaction between Picture Category and Task within dorsal visual-associative regions, inferior parietal, and dorsolateral and medial prefrontal cortices: during the word categorization task, activation was increased in these regions when the words were overlaid over erotic as compared to romantic pictures. During the picture categorization task, activity in these areas was relatively decreased when categorizing erotic as compared to romantic pictures. Thus, the emotional intensity of the pictures strongly affected brain regions devoted to the control of task-related word or picture processing. These findings are discussed with respect to the interplay of obligatory stimulus processing with task-related attentional control mechanisms.